Designing a Model for the Strategic Development of Human Resources in Nationwide Judiciaries Using Fuzzy TOPSIS Approach - HASHEMZEHI, ELAHEH; BEHESHTIFAR, MALIKEH; NIKPOUR, MOHAMMADAMIN (The journal of contemporary issues in business and government, 2021)
The present study was an attempt to design a model for the strategic enhancement of human resources in judiciaries across the country using fuzzy TOPSIS approach. The present research is applied in terms of purpose and exploratory in terms of approach. The Cochran’s formula for limited sample populations was used to select samples from the statistical population. Based on this formula, the number of samples was determined as 365 participants and sample members were selected through multi-stage cluster sampling. The results of content analysis indicated that the model of strategic enhancement of human resources in nationwide judiciaries is comprised mainly of ninety-eight concepts, eighteen categories and six dimensions. The results demonstrated that the most significant inhibitors are “resistance of organizations to change”, “lack of institutionalization of knowledge concerning management culture in the subsets”, “inappropriate long-term policy for human resources”, “inadequate support for managers”, “reduction in motivational factors among employees”, “weak support from senior managers”, “absence of a proper context for monitoring, refining and training employees”, and “inaccurate definition and improper implementation of support mechanisms”. The results further demonstrated that the most important motivating factors are “explaining the role and position of each employee in advancing the goals of the group”, “creating a context for employee self-control and self-management”, “creating a spirit of cooperation and teamwork” and “establishing a logical relationship with performance results”.